MCL-1 is modulated in Crohn’s disease fibrosis by miR-29b via IL-6 and IL-8 - Nijhuis, Anke (2017)
The miR-29 family is involved in fibrosis in multiple organs, including the intestine where miR-29b facilitates TGF-β-mediated up-regulation of collagen in mucosal fibroblasts from Crohn’s disease (CD) patients. Myeloid cell leukemia-1 (MCL-1), a member of the B-cell CLL/Lymphoma 2 (BCL-2) apoptosis family, is involved in liver fibrosis and is targeted by miR-29b via its 3’-UTR in cultured cell lines. We investigate the role of MCL-1 and miR-29b in primary intestinal fibroblasts and tissue from stricturing CD patients. Transfection of CD intestinal fibroblasts with pre-miR-29b resulted in a significant increase in the mRNA expression of MCL-1 isoforms [MCL-1Long (L)/Extra Short (ES) and MCL-1Short (S)], although MCL-1S was expressed at significantly lower levels. Western blotting predominantly detected the anti-apoptotic MCL-1L isoform, and immunofluorescence showed that staining was localised in discrete nuclear foci. Transfection with pre-miR-29b or anti-miR-29b resulted in a significant increase or decrease, respectively, in MCL-1L foci. CD fibroblasts treated with IL-6 and IL-8, inflammatory cytokines upstream of MCL-1, increased the total mass of MCL-1L-positive foci. Furthermore, transfection of intestinal fibroblasts with pre-miR-29b resulted in an increase in mRNA and protein levels of IL-6 and IL-8. Finally, immunohistochemistry showed reduced MCL-1 protein expression in fibrotic CD samples compared to non-stricturing controls. Together, our findings suggest that induction of MCL-1 by IL-6/IL-8 may surmount any direct down-regulation by miR-29b via its 3’-UTR. We propose that an anti-fibrotic miR-29b/IL-6 IL-8/MCL-1L axis may influence intestinal fibrosis in CD. In the future, therapeutic modulation of this pathway might contribute to the management of fibrosis in CD.